Care friendliness in adolescent sexual and reproductive health services in Mexico and a characterisation of their clients. (6th June 2022) - García‐Bello, Luis Alberto; Heredia‐Pi, Ileana Beatriz; Zavala‐Arciniega, Luis; Paz‐Ballesteros, Wayra; Velázquez‐Viamonte, Ailen; Serván‐Mori, Edson
Abstract: Background: Sexual and reproductive health (SRH) is a very important issue in public health programs in low ‐and middle‐income countries (LMICs). Health services that meet specific and differentiated needs of adolescents are increasingly relevant in LMICs. To provide quality services, it is necessary to know the profile of its users and the perspective that adolescents have about SRH services aimed at them. Methods: We conducted a cross‐sectional analysis of primary data from a survey of 489 adolescents recruited in 11 primary‐care facilities in the state of Morelos, Mexico. We followed the guidelines outlined in the World Health Organization Quality Assessment Guidebook: A guide to assessing health services for adolescent clients. Data on friendliness of services were obtained through 70 questions divided into 18 characteristics which, in turn, were grouped into five domains: equity, accessibility, acceptability, appropriateness, and effectiveness. The "friendliness" (a proxy for quality of care) of services was measured according to an additive index of friendliness (FI) ranging from 0 (no friendliness) to 1 (maximum friendliness). We also described the socio‐demographic, SRH, and service utilization profiles of clients. Results: The health services analysed were characterised as having low levels of accessibility (FI = 0.62) and effectiveness (FI = 0.77), moderate acceptability (FI = 0.84), and high levels of appropriateness (FI = 0.93) and equity (FI = 0.92). Of the total number of adolescents surveyed, 51% stated that they had initiated a sexual life, 37% did not use any method of protection during their first sexual intercourse and 64% of the adolescents had already experienced a pregnancy. Conclusions: It is essential to improve the accessibility and effectiveness dimensions of adolescent‐friendly services in Mexico. This requires the implementation of strategies specifically designed to promote well‐informed, planned and healthy sexual behaviours that avert risk and vulnerability. Strategies need to consider the profile of the adolescent client population. Highlights: Adolescents shown high risk behaviour, with onset of sexual life and low prevalence of contraceptive use. Adolescent health services must be strengthened by improving their accessibility and effectiveness. Adolescent health services require strategies to attract and retain its target population. It is the responsibility of health systems to provide quality services to meet the specific needs of the adolescent population.